INFORMATION SYSTEMS DEVELOPMENT PLAN FOR STA. TERESA FUNERAL HOMES - Ruby Jane G. Bondad; Elvie Mae B. Bucana; King Maynard S. Castro; Stacey Nicole Marie G. Monta; Glendell R. Jadraque (International Journal of Innovations in Engineering Research and Technology, 2021)
Nowadays, it’s hard to imagine a business without IT infrastructure. Some years ago, most companies wouldn’t even have it because they deem it not business-friendly. Fast forward to today, any company that fails to incorporate IT into their business process is unnoticed by their competition. Consequently, our team has decided to apply two systems that can help to improve the business process and to halt traditional routine of the company. Production Monitoring System (PMS) is responsible for controlling and stabilizing the production line to stop over-production and to check business performance and operation.Moreover, in terms of human power, the primary step once an employee entered to the firm is attendance. It would be a waste of time if manual system will still be applied and can greatly affect one’s performance. Biometric Time and Attendance System (BTAS) should also be implemented. It gives a high level of accuracy and efficiently maintains employee attendance records.Thus, imposing these systems and other computer-related solution can be a great way to eradicate errors and to increase business productivity and performance.